Effect of Dark Pattern on Tourism Industry - Gill, Roopan (My University, 2025)
Dark Patterns are design tricks that manipulate users into making choices they might not genuinely want, by exploiting cognitive biases. Despite their impact, research on these deceptive tactics in the tourism industry remains limited. This study examines how dark patterns influence consumer purchase intentions (PI) and fear of missing out (FOMO) on online travel booking platforms. To do so two experiments are performed. Experiment one tested social proof (activity message, positive testimonial, negative testimonial) across three categories of tourism (package, hotel, flight) using a mixed factorial design. Its results showed that positive testimonials increased purchase intentions, while activity messages heightened FOMO in participants. Experiment two, tested scarcity appeals (countdown timer, limited supply) across the same categories using mixed factorial design. Its results revealed that limited supply scarcity does increase purchase intention more in comparison with countdown timer, but neither scarcity appeal significantly affected FOMO. Experiment three, tested high anchor and low anchor across the same categories u ko sing mixed factorial design. Its low anchor condition produced slightly higher scores compared to the high anchor condition but neither anchor significantly affected FOMO. Findings indicate while positive testimonials and limited supply scarcity and low anchor effectively boost consumers' purchase intentions, their impact on FOMO varies, suggesting room for more targeted and ethical marketing strategies.
Keywords: Dark Patterns; Anchoring Effect; Purchase intention; Fear of missing out; Social proof; Scarcity appeal